Transcriptomics analysis of propiconazole-treated Cochliobolus sativus reveals new putative azole targets in the plant pathogen - Somani, Deepika; Adhav, Ragini; Prashant, Ramya; Kadoo, Narendra Y. (Functional & Integrative Genomics, 2019)
Cochliobolus sativus (anamorph: Bipolaris sorokiniana) is a filamentous fungus from the class Dothideomycetes. It is a pathogen of cereals including wheat and barley, and causes foliar spot blotch, root rot, black point on grains, head blight, leaf blight, and seedling blight diseases. Annual yields of these economically important cereals are severely reduced due to this pathogen attack. Evolution of fungicide resistant pathogen strains, availability of a limited number of potent antifungal compounds, and their efficacy are the acute issues in field management of phytopathogenic fungi. Propiconazole is a widely used azole fungicide to control the disease in fields. The known targets of azoles are the demethylase enzymes involved in ergosterol biosynthesis. Nonetheless, azoles have multiple modes of action, some of which have not been explored yet. Identifying the off-target effects of fungicides by dissecting gene expression profiles in response to them can provide insights into their modes of action and possible mechanisms of fungicide resistance. Moreover it can also reveal additional targets for development of new fungicides. Hence, we analyzed the global gene expression profile of C. sativus on exposure to sub-lethal doses of propiconazole in a time series. The gene expression patterns were confirmed using quantitative reverse transcriptase PCR (qRT-PCR). This study revealed overexpression of target genes from the sterol biosynthesis pathway supporting the reported mode of resistance against azoles. In addition, some new potential targets have also been identified, which could be explored to develop new fungicides and plant protection strategies.
Keywords: Bipolaris sorokiniana; Cochliobolus sativus; Fungicide resistance; Propiconazole; RNA-seq; Transcriptomics analysis

Whole genome sequencing and comparative genomics of Indian isolates of wheat spot blotch pathogen bipolaris sorokiniana reveals expansion of pathogenicity gene clusters - Yadav, Sagar; Raazi, Zarrine; Shivaraj, Sheelavanta Matha; Somani, Deepika; Prashant, Ramya; Kulkarni, Abhijeet; Kumar, Rajeev; Biradar, Suma; Desai, Shreenivas; Kadoo, Narendra (Pathogens, 2023)
Spot blotch is a highly destructive disease in wheat caused by the fungal pathogen Bipolaris sorokiniana (teleomorph, Cochliobolus sativus). It is prevalent in warm and humid areas, including Africa, Asia, Latin America, and the USA. In the present study, twelve isolates of B. sorokiniana were collected from wheat fields in three different geographical locations in India. The pathogenicity of seven sporulating isolates was assessed on `DDK 1025', a spot blotch-susceptible wheat variety under greenhouse conditions. The isolate `D2' illustrated the highest virulence, followed by `SI' and `BS52'. These three isolates were sequenced using the Illumina HiSeq1000 platform. The estimated genome sizes of the isolates BS52, D2, and SI were 35.19 MB, 39.32 MB, and 32.76 MB, with GC contents of 48.48%, 50.43%, and 49.42%, respectively. The numbers of pathogenicity genes identified in BS52, D2, and SI isolates were 2015, 2476, and 2018, respectively. Notably, the isolate D2 exhibited a relatively larger genome with expanded arsenals of Biosynthetic Gene Clusters (BGCs), CAZymes, secretome, and pathogenicity genes, which could have contributed to its higher virulence among the tested isolates. This study provides the first comparative genome analysis of the Indian isolates of B. sorokiniana using whole genome sequencing.
Keywords: Bipolaris sorokiniana; CAZyme; comparative genomics; spot blotch; whole genome sequencing

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics